Type II Collagen Sponges Facilitate Tendon Stem/Progenitor Cells to Adopt More Chondrogenic Phenotypes and Promote the Regeneration of Fibrocartilage-Like Tissues in a Rabbit Partial Patellectomy Model - Wang, Wen; Qin, Shengnan; He, Peiliang; Mao, Wei; Chen, Liang; Hua, Xing; Zhang, Jinli; Xiong, Xifeng; Liu, Zhihe; Wang, Pengzhen; Meng, Qingqi; Dong, Fei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Objective: Fibrocartilage transition zone(FC) is difficult to regenerate after surgical re-attachment of tendon to bone. Here, we investigated whether type II collagen-sponges(CII-sponges) facilitated tendon stem/progenitor cells(TSPCs) to adopt chondrogenic phenotypes and further observed if this material could increase the FC areas in bone-tendon junction(BTJ) injury model. Methods: CII-sponges were made as we previously described. The appearance and pore structure of CII-Sponges were photographed by camera and microscopies. The viability, proliferation and differentiation of TSPCs were examined by LIVE/DEAD assay, AlamarBlue, and PKH67 in vitro tracking. Subsequently, TSPCs were seeded in CII-sponges, Matrigel, Monolayer and induced under chondrogenic medium for 7 or 14 days before being harvested for qPCR or being transplanted into nude mice to examine the chondrogenesis of TSPCs. Lastly, partial patellectomy(PPT) was applied to establish the bone-tendon junction injury model. CII-sponges were interposed between the patellar fragment and tendon, and histological examination was used to assess the FC regeneration at BTJ after surgery at 8 weeks. Results: CII-sponges were like sponges with interconnected pores. TSPCs could adhere, proliferate and differentiate in this CII-sponge up to 14 days at least. Both qPCR and immunostaining data showed that compared with TSPCs cultured in monolayer or Matrigel, cells in CII-sponges group adopted more chondrogenic phenotypes with an overall increase of chondrocyte-related genes and proteins. Furthermore, in PPT injured model, much more new formed cartilage-like tissues could be observed in CII-sponges group, evidenced by a large amount of positive proteoglycan expression and typical oral or round chondrocytes in this area. Conclusion: Our study showed CII-sponges facilitated the tendon stem/progenitor cells to differentiate towards chondrocytes and increased the area of fibrocartilage transition zones, which means CII-sponges are meaning for the reconstruction of fibrocartilage transition zone at bone tendon junction. However, the link between the two phenomenon requires further research and validation.